Functional Near-Infrared Spectroscopy as Promising Method for Studying Cognitive Functions in Children - Leonid M. Yatsyk; George A. Karkashadze; Viktor V. Altunin; Inessa A. Povalyaeva; Pavel A. Prudnikov; Elena A. Vishneva; Elena V. Kaytukova; Kamilla E. Efendieva; Leila S. Namazova-Baranova ("Paediatrician" Publishers LLC, 2023)
The description of new promising method of functional neuroimaging, functional near-infrared spectroscopy (fNIRS), is presented. General information on functional tomography and its features in children are given. Brief description on the history of fNIRS development, the method itself, its advantages and disadvantages are covered. fNIRS implementation areas in science and clinical practice are clarified. fNIRS features are described, and the role of this method among others in functional tomography is determined. It was noted that fNIRS significantly complements other research and diagnostic methods, including functional magnetic resonance imaging, electroencephalography, induced potentials, thereby expanding the range of scientific and clinical issues that can be solved by functional neuroimaging.